Customer Satisfaction as Mediator of eWOM and Social Media Marketing Effects on Purchase Intention in Indonesia’s Fitness Industry - Christophorus Aditya Sunu Pratama; Maria Apsari Sugiat (Jurnal Ilmiah Manajemen Kesatuan, 2025)
The fitness industry in Indonesia has undergone a rapid transformation, particularly after the COVID-19 pandemic, which heightened public interest in health and home-based exercise. This shift has encouraged brands like Gymfitnessindo to adopt digital marketing strategies to influence consumer behavior. This study aims to analyze the impact of Electronic Word of Mouth (eWOM) and Social Media Marketing (SMM) on Purchase Intention, with Customer Satisfaction as a mediating variable and ICT Effectiveness and Endorsement as moderating variables. A quantitative research design was used, collecting data from 220 respondents via purposive sampling using Google Forms. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that eWOM and SMM do not directly affect Purchase Intention. However, both significantly influence Purchase Intention indirectly through Customer Satisfaction. Conversely, ICT Effectiveness and Endorsement do not significantly moderate the relationship between Customer Satisfaction and Purchase Intention. The study concludes that digital marketing strategies are only effective in influencing Purchase Intention when mediated by Customer Satisfaction. This highlights the critical role of satisfaction in the digital purchase journey, especially in high-involvement products such as fitness equipment.